Ran GTPase: A Key Player in Tumor Progression and Metastasis - Boudhraa, Zied; Carmona, Euridice; Provencher, Diane; Mes-Masson, Anne-Marie (Frontiers in Cell and Developmental Biology, 2020)
Ran GTPase is a member of the Ras superfamily. Like all the GTPases, Ran cycles between an active (GTP-bound) and inactive (GDP-bound) state. However, Ran lacks the CAAX motif at its C-terminus, a feature of other small GTPases that ensure a plasma membrane localization, and largely traffics between the nucleus and the cytoplasm. Ran regulates nucleo-cytoplasmic transport of molecules through the nuclear pore complex and controls cell cycle progression through the regulation of microtubule polymerization and mitotic spindle formation. The disruption of Ran expression has been linked to cancer at different levels, from cancer initiation to metastasis. In the present review we dissect the contribution of Ran in the acquisition of three hallmarks of cancer, namely proliferative signaling, resistance to apoptosis and invasion/metastasis, and highlight its prognostic value in cancer patients. In addition, we discuss the use of this GTPase as a therapeutic target in cancer.